2015
DOI: 10.1515/hepo-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic response of Capsicum interspecific hybrids and capsaicinoid characteristics of DH lines

Abstract: Summary In the research on induced androgenesis, eight groups of plants, the progeny of interspecific hybrid of Capsicum frutescens L. x C. annuum L., were used. Half of them were standard hard-flesh forms, while the others have represented SS or Ss genotype conditioning the soft flesh of ripe fruit. Anthers from the plants of six groups produced mixoploid callus and the DNA content ranged from 1C to 16C. Three groups formed embryos which converted into plants. The total number of regenerants was 19, included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…These findings are in alignment with previous findings that reported the effect of donor plants (Cheng et al 2013), microspore developmental stage (Parra-Vega et al 2013a), culture medium (Irikova et al 2011a;Nowaczyk et al 2016;Ata et al 2019;, growing conditions and age (Irikova et al 2011b;Parra-Vega et al 2013b;Popova et al 2016;. Niklas-Nowak et al (2012) observed that the significant differences were seen in the androgenic response of tested genotypes of individual plants and confirmed that the donor plant genotype is a critical factor in determining the effectiveness of androgenesis in pepper, which is in coherence with our findings.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings are in alignment with previous findings that reported the effect of donor plants (Cheng et al 2013), microspore developmental stage (Parra-Vega et al 2013a), culture medium (Irikova et al 2011a;Nowaczyk et al 2016;Ata et al 2019;, growing conditions and age (Irikova et al 2011b;Parra-Vega et al 2013b;Popova et al 2016;. Niklas-Nowak et al (2012) observed that the significant differences were seen in the androgenic response of tested genotypes of individual plants and confirmed that the donor plant genotype is a critical factor in determining the effectiveness of androgenesis in pepper, which is in coherence with our findings.…”
Section: Discussionsupporting
confidence: 94%
“…Variation for fruit morphological and agronomical traits observed between genotypes of Stryama, Zlaten medal 7, and Victoria varieties background and similar observations have been observed in previous studies in regard to fruit morphological traits variation among androgenic lines of similar background (Shrestha et al 2011;Luitel et al 2012;Shmykova et al 2014;Trajkova and Koleva-Gudeva 2017). The breeding value of different pepper androgenic material has been observed by many authors and promising breeding lines have been created for enhanced fruit quality (Shrestha et al 2011;Luitel and Kang, 2013b;Nowaczyk et al 2014;, improved productivity, plant and fruit traits (Koleva-Gudeva and Trajkova 2012;Luitel et al 2012;Todorova et al 2013;Shmykova et al 2014;Trajkova and Koleva-Gudeva 2017;. Applications of pepper androgenesis have not only been limited to fruit quality and fruit morphological traits, but have also been useful in creating DH lines that have resistance against economically important viral, bacterial (Hwang et al 1998), and fungal diseases (Todorova et al 2013), and nematodes (Ö cal et al 2019;Shimira et al 2019).…”
Section: Discussionsupporting
confidence: 84%
“…Higher visual and taste quality, fruit firmness, dry matter content, total soluble content, titratable acidity, phenolic content, and antioxidant activity were exhibited in pepper DHs (Luitel and Kang, 2013b). Nowaczyk et al (2014) proved that DH technology can be successfully used for the rapid genetic stabilization of soft-flesh Capsicum spp. recombinants.…”
Section: Application Of Anther Culture In Pepper-breeding Programsmentioning
confidence: 86%
“…Nowaczyk et al [54] used DH technology to improve the shelf life of soft-flesh Capsicum spp. recombinants.…”
Section: Development Of Capsicum Haploidsmentioning
confidence: 99%